2021
DOI: 10.3390/medicina57090993
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Positive and Negative Life Changes in Testicular Cancer Survivors

Abstract: Background and objectives: Despite a generally good prognosis, testicular cancer can be a life-altering event. We explored perceived positive and negative life changes after testicular cancer in terms of frequency, demographic and disease-related predictors, and associations with depression and anxiety. Materials and methods: All testicular cancer survivors receiving follow-up care at two specialized outpatient treatment facilities were approached at follow-up visits or via mail. We assessed a total of N = 164… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Symptom burden: Memorial Symptom Assessment Scale—Short Form (MSAS-SF). Vehling et al, [ 55 ] (same study as above) Germany. Investigate and establish the presence of anxiety and depression in TCS and analyse the influence of correlates.…”
Section: Resultsmentioning
confidence: 99%
“…Symptom burden: Memorial Symptom Assessment Scale—Short Form (MSAS-SF). Vehling et al, [ 55 ] (same study as above) Germany. Investigate and establish the presence of anxiety and depression in TCS and analyse the influence of correlates.…”
Section: Resultsmentioning
confidence: 99%
“…We agree with Taku et al (2021) that the positive and negative consequences of trauma, or the changes resulting from experiencing trauma, are not just the opposite ends of one dimension. Vehling et al (2021) modified the PTGI in their research, with each item asking patients to comment on whether they experienced positive or negative change in that domain. They found that the level of positive change was not related to depression or anxiety experience.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of cancers is a major negative life event. [24] The diagnosis of malignancy and the pain of the cancer itself constitute a strong reminder of the possibility of death, which can easily lead to adverse psychological problems in patients. [25] Notably, when evaluating the relationship between sociodemographic factors and loneliness in patients with hematological malignancies, we found that occupation, family earning, living areas, and times of hospitalization were significantly related to loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of cancers is a major negative life event. [24] The diagnosis of malignancy and the pain of the cancer itself constitute a strong reminder of the possibility of death, which can easily lead to adverse psychological problems in patients. [25]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation